90.2k views
1 vote
Solve for x


\ \textless \ br /\ \textgreater \ x = (1)/(2-(1)/(2-(1)/(2-x) ) ) \: \: \: , (x \\eq 2)
Help me with this!​

User Savagent
by
6.0k points

1 Answer

3 votes

Answer:


x= (3-2x)/(4-3x)

Explanation:

Given:


x=(1)/(2-(1)/(2-(1)/(2-x)))}

Simplify:


\begin{aligned}2-(1)/(2-x) & =(2(2-x)-1)/(2-x)\\\\ & =(3-2x)/(2-x)\end{alilgned}

Therefore:


x=(1)/(2-(1)/((3-2x)/(2-x)))

Simplify:


\begin{aligned}2-(1)/((3-2x)/(2-x)) & =2-(2-x)/(3-2x)\\\\ & =(2(3-2x)-(2-x))/(3-2x)\\\\ & = (6-4x-2+x)/(3-2x)\\\\ & = (4-3x)/(3-2x)\end{aligned}

Therefore:


x & =(1)/((4-3x)/(3-2x))


\textsf{Apply the fraction rule}: \quad (1)/((b)/(c))=(c)/(b)


\implies x& = (3-2x)/(4-3x)

User Ye Liu
by
6.1k points